Transition to adulthood of young people in condition of Intellectual Disability (ICID): a comparative study of the professional's perspective in Norway and Colombia - Castillo, Ursula Hinostroza (2019)
This study aims to compare the perspective of professionals in Norway and Colombia regarding transition to adulthood in young people with Intellectual Disability (ID). A comparative study was carried out to explore how social, political and economic aspects affect the process of transition to adulthood of young people with ID in a developed country (Norway) and in a developing country (Colombia). Data was collected by semi-structured interviews. Transition from school to work was identified as a key aspect in transition to adulthood. Therefore, professionals were selected from education institutions (two participants from each country) and labor insertion institutions (two participants from each country), a total of eight participants. Data was analyzed in NVivo 11 using a thematic analysis approach. As humans are multidimensional beings, this study proposes an innovative analysis approach which combines tools from psychology and social work to be able to analyze this issue in a micro and macro level. The study found that professional's perspective regarding transition to adulthood was similar and converged with main theoretical concepts, in both countries. Further, it was found that practices of strengths perspectives, empowerment and promoting the right of participation in youth, create a positive impact on overall outcome. However, the study found major heterogeneity in the service provision in both countries, probably caused by the fact that Norway has a social democratic welfare state and Colombia has an emerging welfare regime. Nonetheless, it was identified that a major challenge for both countries is the lack of information and awareness about ID. This study is relevant as it is focused on a population who is vulnerable in two conditions: a condition of intellectual disability and the transition to adulthood, which is characterized as a complex, unstable and uncertain period of life. Moreover, it aims to identify supports and challenges youth may face during this transition. This study also shows the importance of interdisciplinary approaches as well as it is a reminder to increase inclusive practices in micro and macro settings.